Idiopathic multicentric Castleman disease: a mysterious case of generalized lymphadenopathy - Sebastian, Nikhil; P. N., Shoaib Nawaz; Ramya Ananthkrishnan; J., Kumanan; Lakshmanan, Archana; Raja, Thirumalairaj (International Journal of Research in Medical Sciences, 2023)
Castleman disease is a syndrome with significant clinico-pathological overlap between malignancy, autoimmune causes and infectious etiologies. It is a spectrum and can vary in extent from unicentric to multicentric disease with generalized lymphadenopathy, organ involvement, constitutional symptoms and cytopenias, and in severity from non-severe to severe disease with TAFRO symptoms. Idiopathic multicentric Castleman disease (iMCD) is a diagnosis of exclusion after multiple causes as per diagnostic criteria are excluded. Treatment varies between the disease severity types with anti-IL 6 antibodies for non-severe disease to cytotoxic chemotherapy agents for severe disease with TAFRO symptoms. We hereby report a case of a non-severe type of iMCD with a prolonged course and delayed arrival at the diagnosis, owing to the rarity of this condition, which stresses the need for a reduced threshold to consider MCD, early in the differential diagnosis. Interestingly there were positive auto-antibodies and elevated IgG4 levels in this patient, but applying strict criteria helps to distinguish the diagnosis.